Pengaruh Perendaman Campuran Klorheksidin 0,5% Dengan Alkohol 70% Terhadap Perubahan Dimensi Bahan Cetak Alginat - Galib, Fitriyah, drg. Noor Hafida Widyastuti, Sp.KG, drg. Nilasary Rochmanita S, MDSc (2015)
Alginate is one of the most frequently used dental materials. Alginate immersion into disinfectant solution could cause its dimensional changesbecause ofits syneresis and imbibitions characteristics 0.5% chlorhexidine -70% alcohol solution was known as effective disinfectant for antivirus, antifungal, antimicrobial, and also biocompatible for oral tissues because of its low toxicity. The purpose of this study was to find out the effect of 0.5% chlorhexidine -70% alcohol solution immersion toward dimensional changes of alginate impression.The sample was cylindrical alginate impression with 25 mm diameter of opened surface and 30 mm diameter of its base (32 samples) in one group with pretest and post test treatment. Radius measurement by sliding caliper were done twice for each sample, before and after it was submerged into 0.5% chlorhexidine -70% alcohol solution for about 10 minutes. The data gained was definet as the data before and after immersion. Dimensional changes were calculated from tube volume(πr2t) differences before and after immersion. The data was analyzed using Pairedt-test, but because thedata was not normally distributed after transformation, then Wilcoxon nonparametric test used as alternative. It can be concluded that immersion into0.5% chlorhexidine -70% alcohol based compound for 10 minutes could couse dimensional change on alginate impression material with p-value p = 0.000 (p<0.05).